(untitled) (Bangladesh Journal of Botany, 2011)
Mesophytic species such as Acacia nilotica, Albizia labeck, Albizia procera, Casuarina equisetifolia, Pithocellobium dulche, Samanea saman and Thespesia populnea were raised in the western coast of Char Kashem under Patuakhali district of Bangladesh. After seven years of planting highest survivability was found in A. labeck followed by P. dulche, C. equisetifolia, S. saman, A. procera, A. nilotica and T. populnea. The mean maximum diameter at breast height was found in S. saman followed by C. equisetifolia, A. procera, A. labeck, P. dulche, A. nilotica and T. populnea. The maximum plant height was found in C. equisetifolia followed by S. saman, A. procera, T. populnea, A. nilotica, A. labeck and P. dulche indicating suitability of all the seven species for plantation at Char Kashem. Key words: Mesophytes; Coastal afforestation; Growth performance; Bangladesh DOI: 10.3329/bjb.v39i2.7488 Bangladesh J. Bot. 39(2): 245-247, 2010 (December)